Analysis of Microstructure Changes for AlSi9Cu3 Alloy Caused by Remelting - Bolibruchová, Dana; Matejka, Marek (Manufacturing Technology Journal, 2018)
The use of recycled or remelted alloys is one of the most common ways to reduce production costs. As the number of remelting increases, also chance of the chemical composition and the microstructure alteration is increasing, which has a major impact on the resulting mechanical properties. The microstructure of recycled alloys mostly affects the presence of iron and its negative effect on casting properties. The paper deals with the degree and the way of influence of the remelting on the microstructure of AlSI9Cu3 alloy with increased iron content to 1.4 wt. %. In the work are progressively evaluated changes of microstructures focused on the morphology and shape of the iron phases, dendritic structure change and pore formation due to remelting on AlSI9Cu3 alloy after natural aging and after the heat treatment (T5). The obtained results point to degradation of the microstructure due to multiple remelting with the possibility of partial improvement when applying heat treatment (T5).
Keywords: AlSi alloy; Remelting; Metallography; Fe phase